Challenges of Small Scale Fish Farmers for Fish Product Sustainability - Elfitasari, Tita; Albert, Albert (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
The aquaculture industry is growing tremendously over the past two decades following the significant decline of the world’s fish catch. Nevertheless, small scale fish farmers are still one of the most vulnerable communities in Indonesia, with low income and limitation in carrying out their fish farming business. In their attempt to carry out successful aquaculture business, small scale fish farmers encounter several challenges that inhibit the fish farmers in ensuring the sustainability of fish products. This research aims to explore challenges and identify internal and external challenges that affect fish farmers’ activities in ensuring fish product sustainability. This research used a quantitative approach by collecting data through questionnaire distribution to small scale fish farmers in Central Java and data was analyzed using statistical analysis package. The findings of this research showed that challenges consist of nine internal and seven external challenges. Result of statistical analysis indicated that internal challenges influenced product sustainability through water quality examination, whereas external challenges influenced product sustainability through two activities, such as giving feed at the right quantity and time, and maintain fish seed quality and availability.